Microscopic Analysis of the Tips of Thin Spinal Needles After Subarachnoid Puncture. Issue 1 (January 1996) - Rosenberg, Per H.; Pitkänen, Mikko T.; Hakala, Pertti; Andersson, Leif C.
Abstract : Background and Objectives: Foreign material may pass unrecognized with the spinal needle into the subarachnoid space. Therefore the tips of three clinically used types of spinal needles—Quincke (27-gauge), two-zone bevel (26-gauge), and Sprotte or pencil point (27-gauge)—were prepared for microscopic analysis after subarachnoid puncture in human cadavers. Methods: Three cadavers were placed in the lateral position, the backs were scrubbed with disinfectant solution containing 0.1% fluorescein, and 12 needles of each type (half of them through an introducer) were inserted via interspaces L2-L5 into the subarachnoid space. Under visual control (spinal canal opened), the needle tips were cut and collected for fluorescence microscopy. Another eight needles of each type (half through an introducer) were inserted, the tips were collected into tubes filled with physiologic saline, and cytocentrifuged smears of the eluted material were made. Results: On microscopy, only one of the two-zone bevel needles and two of the pencil point needles, placed through an introducer, were without attachments. All the others had variable amounts of fluorescence, and visible tissue particles adhered to the tip. The largest particles appeared on two of the Quincke needle tips. Bent tips were seen on 7 of the 12 two-zone bevel needles. The Quincke group had two and the pencil point group no bent needle tips. Clusters of epithelioid cells were seen in the cytocentrifugation smears of Quincke and two-zone bevel needle tips, but only very few cellular clusters were seen in the smears from the pencil point needle tips. Conclusions: Of the three needle types studied, the pencil point type has a tip that best withstands distortion and adherence of foreign material during experimental subarachnoid puncture.